Backward-wave optical parametric oscillators: principles, applications, and recent advancements - Laurell Fredrik; Pasiskevicius Valdas (Journal of the European Optical Society-Rapid Publications)
Backward-wave optical parametric oscillators (BWOPOs) represent a significant advancement in nonlinear optics, offering unique capabilities such as narrowband, highly stable outputs without the need for mirrors or coatings. Leveraging self-established distributed feedback, these devices exhibit exceptional spectral and spatial properties. This paper explores the principles behind BWOPOs, materials and techniques used, and their applications, particularly in mid-infrared lidar systems including CO2 monitoring. Recent developments in cascaded systems and BWOPO waveguides are highlighted, demonstrating the potential of BWOPOs to revolutionize laser technology.